Enhancing Work Environment and Work Relationship for Employee Retention: A Case Study of Project Management Section, Jyo Electronics, Petchaburi - Purayidathil, Joseph; Villavicencio, D.Ed., Salvacion (ABAC ODI JOURNAL Vision. Action. Outcome, 2014)
Companies whose IT departments are overworked and undervalued are at risk for higher turnover. IT employees realize their value in today’s market, especially those with the best certifications. An inability to retain employees in a technology department or company will certainly cost money. It can also result in losing other important employees and clients because of employee frustration and stress when customers’ work is unable to be completed. IT employers’ challenge lies in providing the training to improve their employees’ work, while keeping them engaged and wanting to continue to use that training within the company. The main purpose of this study is on Enhancing Work Environment and Working Relationship for Employee Retention in the Project Management Section of the Company. The study indicates that work environment and working relationship influence the employees’ perception towards employee retention. The researcher used three instruments to gather data from the staff of the PMS of Jyo Electronics. These instruments include the survey questionnaire, observation checklist and interview guideline. The respondents of this research were the 39 staff members of the PMS of Jyo Electronics. Descriptive statistics and t –test were used to analyze the quantitative data in the Pre ODI stage and Post ODI stage. The researcher used the Whole Brain Literacy (WBL) Model to analyze the qualitative data collected through the interviews and observation The results of the study showed that there is a significant difference in respondent’s perception towards employee retention, work environment and working relationship before and after the Organization Development Interventions (ODI). In conclusion, the ODI have impact on Work Environment and Working Relationships in the Project Management Section of Jyo Electronics, Petchaburi. Keywords: work environment, working relationship, employee retention, whole brain literacy (WBL)